2022
DOI: 10.3390/ijerph192114501
|View full text |Cite
|
Sign up to set email alerts
|

The Association between Self-Rated Health and Health Self-Management Ability of Healthcare Undergraduates: The Chain Mediating Roles of eHealth Literacy and Resistance to Peer Influence

Abstract: Health self-management is important for healthcare undergraduates who are at the late adolescent or early adulthood stage, and will play an important part in health promotion for the general population. Previous research has shown that perceived health status affects health self-management. However, few studies have uncovered the mechanism between self-rated health and health self-management among healthcare undergraduates. Based on social ecology theory and Pender’s health promotion model, this study aimed to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 42 publications
(64 reference statements)
0
4
0
Order By: Relevance
“…This suggests that undergraduate nursing students have better health self-management skills, which may be attributed to their professional studies. However, the health self-management skills of the nursing undergraduates were poorer than those of the healthcare undergraduates [ 10 ], and this infers a need to strengthen this trait.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This suggests that undergraduate nursing students have better health self-management skills, which may be attributed to their professional studies. However, the health self-management skills of the nursing undergraduates were poorer than those of the healthcare undergraduates [ 10 ], and this infers a need to strengthen this trait.…”
Section: Discussionmentioning
confidence: 99%
“…University students are especially encouraged to cultivate healthy self-management skills because they can keep their minds healthy, boost the immune system, and lower the effects of stress [ 9 ]. However, studies on health self-management among university students, especially nursing students, are limited, albeit published studies have shown a need to strengthen these skills among this group [ 10 ]. As the preparatory workforce for future clinical care, developing good health self-management skills in undergraduate nursing students will lead to good health outcomes for both students and professional experts in patient health coaching [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the current study, SPSS 25 ( 46 ) (IBM, Armonk, NY, United States) and Model 6 of PROCESS Macro ( 47 ) were used to analyze the survey data. Descriptive statistics were used to analyze the sample characteristics.…”
Section: Methodsmentioning
confidence: 99%
“…The path analysis between self-rated health and negative emotions reveals a significant effect of self-rated health. Studies have shown that the overall self-rated health score is positively correlated with the total health literacy score; the higher the self-rated health score, the higher the individual's level of health literacy (74). Individuals with high health literacy are more likely to adopt positive health behaviors and coping strategies when facing mental health issues.…”
Section: The Mediating Role Of Self-rated Healthmentioning
confidence: 99%